2020
DOI: 10.1155/2020/8534028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different IOL Types in the Flanged IOL Fixation Technique

Abstract: Purpose. To compare short-term clinical outcomes between two different intraocular lens (IOL) types in the flanged IOL fixation technique. Methods. This study was a retrospective case series and included the patients who underwent flanged IOL fixation between June 2017 and July 2018 at the Hiroshima University Hospital. Two different 3-piece IOLs (NX-70 and PN6A) were used. Recipients of NX-70 and PN6A IOLs were classed into groups 1 (15 eyes) and 2 (25 eyes), respectively. Patient characteristics, surgical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 14 publications
0
23
0
Order By: Relevance
“…It is interesting to note that in the earlier study by Yamane et al, use of 6-mm IOLs, including ZA9003, PN6A (Kowa, Tokyo, Japan), and MA60MA (Alcon laboratories, Fort worth, TX), resulted in a 7-times higher incidence of pupillary optic capture compared with X-70 (Santen, Osaka, Japan) IOLs, which have a 7-mm optic diameter (14% vs. 2% incidence, respectively). 4 Miura et al 10 also reported similar outcomes. Although the 7-mm optics could be more advantageous to avoid pupillary optic capture compared with 6-mm optics, the X-70 is available only in Japan.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…It is interesting to note that in the earlier study by Yamane et al, use of 6-mm IOLs, including ZA9003, PN6A (Kowa, Tokyo, Japan), and MA60MA (Alcon laboratories, Fort worth, TX), resulted in a 7-times higher incidence of pupillary optic capture compared with X-70 (Santen, Osaka, Japan) IOLs, which have a 7-mm optic diameter (14% vs. 2% incidence, respectively). 4 Miura et al 10 also reported similar outcomes. Although the 7-mm optics could be more advantageous to avoid pupillary optic capture compared with 6-mm optics, the X-70 is available only in Japan.…”
Section: Discussionmentioning
confidence: 69%
“…Pupillary optic capture after flanged IOL scleral fixation is a relatively common postoper-ative complication, and its incidence in this study was similar to that of previous studies. 4,9,10 Although the mechanism of pupillary optic capture is not fully understood, axial length, ACD, and IOL tilt have been suggested as possible causes of the complication after sutured scleral IOL fixation. [12][13][14] For flanged IOL fixation, construction of the nasal and temporal scleral tunnels is a critical step because both haptics are directly fixed to the sclera instead of the suture thread.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We marked off two 1-mm points from which the haptics passed through the sclera as the flanged positions to achieve better IOL centration. Given that the haptic length was different in varying models of IOLs, such as 8.6 mm in NX-70 (Santen, Osaka, Japan) and 8.2 mm in PN6A (Kowa, Tokyo, Japan) [ 18 ], the first step can be skipped when using IOLs with shorter haptics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they stated that younger patients seemed to be more prone to movement of the iris; however, the reasons remain unclear. 8 Miura et al 13 reported that peripheral iridotomy may reduce the pressure difference between the anterior and posterior chambers, thus, making iris capture less likely to occur in 6-mm optic IOLs. Moreover, the 7-mm optic IOL may not need a peripheral iridotomy preventing for iris capture.…”
Section: Discussionmentioning
confidence: 99%